A supported platinum-based catalyst for oxygen reduction reaction in chloride-containing electrolyte and a preparation method and application thereof
Patent Information
- Application Number
- CN202610986192.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-20
AI Technical Summary
然而,单独的氮掺杂碳载体或未优化的Pt/碳复合催化剂在含Cl-电解液中仍难以同时兼顾Pt颗粒分散性、活性位点稳定性以及含氯离子环境下的长时氧还原性能
[0026](1)本发明采用具有有序介孔结构的M-N-C载体负载Pt,Pt颗粒分散于M-N-C载体的外表面、孔口和/或介孔孔道内。介孔孔道有利于Pt颗粒分散并改善局部传质环境,从而减轻Cl-对Pt活性位点的毒化作用及对催化剂骨架的破坏。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a supported platinum-based catalyst for oxygen reduction reaction of chloride-containing electrolytes, its preparation method and application. The catalyst is suitable for chloride-containing aqueous electrolyte systems such as sodium chloride aqueous solution, simulated seawater or natural seawater, and is particularly suitable for the air electrode of metal-air batteries under chloride-containing electrolyte conditions. Background Technology
[0002] The rising demand for energy and the increasing severity of environmental problems have driven the development of new clean energy technologies. Electrochemical systems based on the oxygen reduction reaction, such as metal-air batteries and fuel cells, have attracted widespread attention in the fields of energy storage and energy conversion due to their high energy density and safety and environmental friendliness. In particular, magnesium-air batteries, aluminum-air batteries, and zinc-air batteries have potential applications in marine energy, marine equipment, and emergency power supply scenarios due to their ability to use neutral saline or seawater as electrolytes.
[0003] However, electrochemical devices using chloride-containing electrolytes, such as magnesium-air batteries, still face challenges such as slow cathode reaction kinetics and insufficient catalyst durability. Complex gas-liquid-solid three-phase interface reactions and slow oxygen reduction reaction kinetics lead to increased electrode overpotential, limiting energy conversion efficiency. Simultaneously, the Cl- in the electrolyte... - It has strong adsorption and coordination capabilities, and is easily adsorbed onto the catalytic active sites of noble metals such as Pt, which can lead to poisoning of active sites, electrode corrosion and side reactions, resulting in the decay of oxygen reduction activity and a reduction in battery life.
[0004] Platinum-based catalysts typically exhibit high oxygen reduction catalytic activity, but in chloride-containing electrolytes, Pt active sites are susceptible to Cl-induced degradation. - Adsorption affects catalytic activity and stability. In some reported approaches, researchers have attempted to improve the stability of Pt-based catalysts through Pt alloying, core-shell structure design, or surface modification. However, for solutions containing Cl-, such as sodium chloride aqueous solutions, simulated seawater, or natural seawater... - For aqueous electrolytes, the above-mentioned methods may still face challenges such as numerous preparation steps, limited Pt utilization, and Cl... - Problems include insufficient adsorption and poisoning inhibition or long-term performance degradation.
[0005] Nitrogen-doped carbon materials and transition metal-nitrogen-carbon materials possess high specific surface areas, tunable pore structures, and coordination sites, showing potential applications in oxygen reduction reactions. However, nitrogen-doped carbon supports alone or unoptimized Pt / carbon composite catalysts exhibit limitations in Cl-containing reactions. -It remains difficult to simultaneously achieve optimal Pt particle dispersibility, active site stability, and long-term oxygen reduction performance in chloride-containing environments using electrolytes. Therefore, there is an urgent need to develop a method that can suppress Cl- in chloride-containing electrolytes. - Poisoning, maintaining high oxygen reduction activity and long-term stability of supported platinum-based catalysts. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a supported platinum-based catalyst for oxygen reduction reactions in chloride-containing electrolytes, its preparation method, and its application. The catalyst possesses an ordered mesoporous structure and MN... x Using MNC materials with coordination centers as supports and loading Pt particles on them, they can exhibit high oxygen reduction catalytic activity and stability in chloride-containing electrolytes.
[0007] The technical solution adopted in this invention is as follows: A mesoporous template is used to induce the formation of a MNC carrier with an ordered mesoporous structure and MN coordination centers. Pt particles are then loaded onto this carrier, dispersing the Pt particles on the outer surface, pores, and / or mesoporous channels of the MNC carrier. Simultaneously, the MN contained in the MNC carrier is utilized... x The metal-support interaction between the coordination center and Pt particles modulates the electronic structure of Pt, thus synergistically improving the catalyst's performance in Cl-containing environments by regulating both the support's pore structure and electronic structure. - Oxygen reduction stability in electrolytes.
[0008] This invention relates to a supported platinum-based catalyst for the oxygen reduction reaction in chloride-containing electrolytes. The catalyst comprises a mesoporous MNC support and Pt particles supported on the MNC support, wherein M is at least one of Fe, Co, Ni, Mn, Cu, and Zn, preferably Fe and / or Co; N is nitrogen; and the MNC support contains MN. x The coordination center, x represents the coordination number of M and N, and the specific value of x is not limited, generally 2-5. The Pt particles are dispersed on the outer surface, pores and / or mesoporous channels of the MNC support. The mass fraction of Pt in the catalyst is 5-50 wt%, preferably 10-30 wt%.
[0009] In this invention, the ordered mesoporous structure facilitates the dispersion of Pt particles and the mass transfer of reactants, and can regulate the Cl content. - The local diffusion environment of the electrolyte near the Pt active sites; the MN x The coordination center can interact with Pt particles to form a metal-support interaction, modulating the electronic structure of Pt particles and weakening the Cl- support. -Adsorption at Pt active sites improves the oxygen reduction stability of the catalyst in chloride-containing electrolytes.
[0010] This invention also provides a method for preparing the above-mentioned supported platinum-based catalyst, comprising the following steps:
[0011] (1) Add the precursor of metal element M and the heterocyclic compound with bidentate nitrogen ligand to the alcohol-water mixture and disperse by ultrasonication to obtain mixed solution A;
[0012] (2) Add and disperse the nitrogen-containing compound and mesoporous template into the mixed solution A, and stir to mix them evenly to obtain mixed solution B;
[0013] (3) After drying the mixed solution B, a solid powder was obtained; the solid powder was pyrolyzed at high temperature under an inert atmosphere, and then washed and dried with hydrofluoric acid to obtain an MNC carrier with an ordered mesoporous structure.
[0014] (4) Add the MNC carrier and H2PtCl6·6H2O or its aqueous solution to a mixed solution of ethylene glycol and water, sonicate and stir to obtain solution C, and add NaOH solution to adjust the pH value of solution C to not less than 10;
[0015] (5) Place solution C in a microwave reactor and heat to 400 K. Then add nitric acid to adjust the pH of the reaction system to no higher than 2. Stir for 2-5 min and then cool naturally. Filter, wash and vacuum dry to obtain Pt / MNC precursor powder.
[0016] (6) The Pt / MNC precursor powder is heated in a reducing atmosphere to obtain the Pt / MNC catalyst.
[0017] The precursor of the metal element M in step (1) includes at least one of sulfate, chloride, acetate, and aromatic organometallic compound; the metal element M includes at least one of Fe, Co, Ni, Mn, Cu, and Zn, preferably Fe and / or Co.
[0018] The heterocyclic compound with bidentate nitrogen ligands in step (1) includes at least one of o-phenanthroline and bipyridine; the molar ratio of the metal element M to the heterocyclic compound with bidentate nitrogen ligands is 1:(1~6), preferably 1:2~1:3.
[0019] The nitrogen-containing compound in step (2) is selected from one or more of 2-methylimidazole, dicyandiamide, urea, pyridine, pyrrole, and melamine; the molar ratio of the metal element M precursor to the nitrogen-containing compound is 1:6 to 1:60, preferably 1:30 to 1:45.
[0020] The mesoporous template in step (2) is selected from at least one mesoporous silica template among SBA-15, MCM-48, and KIT-6. The mesoporous template is used to induce the formation of an ordered mesoporous channel structure that can buffer Cl⁻ diffusion.
[0021] The pyrolysis atmosphere in step (3) is nitrogen or argon, the pyrolysis temperature is 800~1000℃, the pyrolysis time is 1.5~5h, and the heating rate from room temperature to the pyrolysis temperature is 2~5℃ / min.
[0022] The reducing atmosphere in step (6) is a mixture of H2 / N2 or H2 / Ar, and the heating is a two-stage heat treatment. The first-stage treatment temperature is 200~400℃ to achieve preliminary reduction, and the second-stage reduction treatment temperature is 600~800℃ to establish a strong interaction between the metal and the carrier. The holding time for each temperature plateau is 1.5~2 h, and the heating rate from room temperature to the corresponding treatment temperature is 2~5℃ / min.
[0023] This invention also provides the application of the above-mentioned supported platinum-based catalyst in the catalysis of oxygen reduction reactions in chloride-containing electrolytes. The chloride-containing electrolyte is preferably an aqueous solution of sodium chloride, simulated seawater, or natural seawater, and the chloride-containing electrolyte contains Cl... - The concentration is 0.1~1.0 mol / L, or the sodium chloride electrolyte is an aqueous solution of 0.5~5 wt%.
[0024] This invention also provides the application of the above-mentioned supported platinum-based catalyst in the air electrode of a metal-air battery. The metal-air battery uses a chloride-containing electrolyte, preferably an aqueous solution of sodium chloride, simulated seawater, or natural seawater; the metal-air battery is preferably a magnesium-air battery.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] (1) In this invention, Pt is loaded onto a MNC carrier with an ordered mesoporous structure. The Pt particles are dispersed on the outer surface, pores, and / or mesoporous channels of the MNC carrier. The mesoporous channels facilitate the dispersion of Pt particles and improve the local mass transfer environment, thereby reducing Cl. - The poisoning effect on Pt active sites and the destruction of the catalyst framework.
[0027] (2) The MNC carrier of the present invention contains MN x Coordination center. MN x The coordination center can form a strong metal-support interaction with Pt particles, modulate the electronic structure of Pt particles, and weaken the Cl-. - Adsorption at Pt active sites improves the stability of Pt particles in chloride-containing environments.
[0028] (3) This invention utilizes the spatial confinement / diffusion buffering effect of ordered mesoporous channels and MN x The synergistic effect of the Pt metal-support interaction enables the catalyst to exhibit both high oxygen reduction activity and chlorine resistance in chloride-containing electrolytes.
[0029] (4) The Pt / MNC catalyst prepared in this invention exhibits excellent chlorine resistance in 3.5 wt% NaCl solution. In the 12 h potentiostatic stability test, the current retention rates of the Pt / Fe-NC and Pt / Co-NC catalysts reached 93.86% and 93.37%, respectively, which are significantly higher than the 73.62% of the Pt / NC catalyst and the 72.69% of the commercial Pt / C catalyst, indicating that the transition metal MN in the MNC support... x The site and ordered mesoporous structure have a synergistic effect on improving chlorine resistance.
[0030] (5) The Pt / MNC catalyst prepared in this invention can be used in chloride-containing electrolyte systems such as sodium chloride aqueous solution, simulated seawater, or natural seawater, and is particularly suitable for the air electrode of magnesium-air batteries. A magnesium-air battery assembled using the catalyst as the cathode catalyst achieves a performance of 10 mA / cm². 2 The ability to continuously discharge for more than 350 hours at a constant current density indicates its good application potential in battery devices containing chloride ion electrolytes. Attached Figure Description
[0031] Figure 1 TEM images of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1, (a1-a2) 20% Pt / Fe-NC, (b1-b2) 20% Pt / Co-NC, (c1-c2) 20% Pt / NC;
[0032] Figure 2 XRD patterns of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1;
[0033] Figure 3 BET plots for the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1;
[0034] Figure 4LSV curves of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and the commercial 20% Pt / C catalyst in 0.1 M KOH solution;
[0035] Figure 5 LSV curves of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and the commercial 20% Pt / C catalyst in 3.5 wt% NaCl solution;
[0036] Figure 6 Comparison of the 12-h potentiostatic stability test results of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and the commercial 20% Pt / C catalyst in 0.1 M KOH solution;
[0037] Figure 7 Comparison of the potentiostatic stability of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Example 1, Example 2, and Comparative Example 1, and the commercial 20% Pt / C catalyst in 3.5 wt% NaCl solution for 12 h;
[0038] Figure 8 The polarization curves are shown for magnesium-air batteries assembled using the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and a commercial 20% Pt / C catalyst as air electrode catalysts.
[0039] Figure 9 The discharge step curves of magnesium-air batteries assembled using 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and a commercial 20% Pt / C catalyst as air electrode catalysts are shown.
[0040] Figure 10 Magnesium-air batteries were assembled using 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, and a commercial 20% Pt / C catalyst as air electrode catalysts. The performance was measured at 10 mA / cm². 2 Durability test under continuous discharge for 350 h. Detailed Implementation
[0041] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0042] Those skilled in the art should recognize that this embodiment is only used to illustrate the present invention and is not intended to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.
[0043] Unless otherwise stated, "20% Pt / Fe-NC, 20% Pt / Co-NC, 20% Pt / NC" in this invention refers to a theoretical mass fraction of Pt of 20 wt% based on the total mass of the target catalyst, and "commercial 20% Pt / C catalyst" refers to a commercial Pt / C catalyst with a mass fraction of 20 wt%.
[0044] Example 1
[0045] A Pt / MNC catalyst, the preparation method of which specifically includes the following preparation steps:
[0046] Dissolve 0.16 g of ferrous sulfate heptahydrate and 0.27 g of o-phenanthroline in 25 mL of an aqueous ethanol solution (V 乙醇 :V 水 The solution was mixed by sonication for 10 min (ratio 1:1). Then, 1.98 g of 2-methylimidazole and 0.5 g of SBA-15 were added to the mixture, and the mixture was stirred for 1 h to ensure thorough mixing. The resulting solution was evaporated in a water bath at 70°C to obtain a red viscous substance, which was then dried overnight in an oven at 70°C to obtain a red solid. The red solid was then thoroughly ground to obtain the precursor.
[0047] The precursor was heated to 900°C in a nitrogen-filled tube furnace at a heating rate of 5°C / min and held at 900°C for 3 h. It was then cooled to room temperature at a rate of 5°C / min to obtain a black powder. The black powder was immersed in a 15 wt% HF solution for 12 h to etch the SBA-15 template. Finally, it was washed with deionized water until neutral and dried overnight under vacuum at 70°C to obtain the Fe-NC material.
[0048] 0.3 g of Fe-NC material and 4.08 mL of H2PtCl6·6H2O aqueous solution (concentration 50 g / L) were dissolved in 70 mL of a mixed solution of ethylene glycol and water (V 乙二醇 :V 水The mixture was prepared with a 9:5 ratio of NaOH solution and thoroughly mixed. Then, an appropriate amount of 10 wt% NaOH solution was added to adjust the pH of the mixture to above 10. The thoroughly mixed solution was placed in a microwave reactor and heated to 400 K. Nitric acid was then added to adjust the pH of the reaction system to no higher than 2. After stirring for 2-5 minutes, the mixture was allowed to cool naturally, filtered, washed, and dried overnight under vacuum.
[0049] The dried solid powder was heated to 300℃ in a H2 / N2 mixture at a heating rate of 5℃ / min and held for 2h. Then the temperature was increased to 700℃ and held for 2h. The temperature was then lowered to room temperature to obtain a 20% Pt / Fe-NC catalyst.
[0050] Example 2
[0051] A Pt / MNC catalyst, the preparation method of which specifically includes the following preparation steps:
[0052] Dissolve 0.12 g of cobalt acetate and 0.27 g of o-phenanthroline in 25 mL of an aqueous ethanol solution (V 乙醇 :V 水 The solution was mixed by sonication for 10 min (ratio 1:1). Then, 1.98 g of 2-methylimidazole and 0.5 g of SBA-15 were added to the mixture, and it was stirred for 1 h to ensure thorough mixing. The resulting solution was evaporated in a water bath at 70°C to obtain a brown viscous substance. This substance was then dried overnight in an oven at 70°C to obtain a brown solid. The brown solid was then thoroughly ground to obtain the precursor.
[0053] The precursor was heated to 900°C in a nitrogen-filled tube furnace at a heating rate of 5°C / min and held at 900°C for 3 h. It was then cooled to room temperature at a rate of 5°C / min to obtain a black powder. The black powder was immersed in a 15 wt% HF solution for 12 h to etch the SBA-15 template. Finally, it was washed with deionized water until neutral and dried overnight under vacuum at 70°C to obtain the Co-NC material.
[0054] 0.3 g of Co-NC material and 4.08 mL of H2PtCl6·6H2O aqueous solution (concentration 50 g / L) were dissolved in 70 mL of a mixed solution of ethylene glycol and water (V 乙二醇 :V 水 The mixture was prepared with a 9:5 ratio of NaOH solution and thoroughly mixed. Then, an appropriate amount of 10 wt% NaOH solution was added to adjust the pH of the mixture to above 10. The thoroughly mixed solution was placed in a microwave reactor and heated to 400 K. Nitric acid was then added to adjust the pH of the reaction system to no higher than 2. After stirring for 2-5 minutes, the mixture was allowed to cool naturally, filtered, washed, and dried overnight under vacuum.
[0055] The dried solid powder was heated to 300℃ in a H2 / N2 mixture at a heating rate of 5℃ / min and held for 2h. Then the temperature was increased to 700℃ and held for 2h. The temperature was then lowered to room temperature to obtain a 20% Pt / Co-NC catalyst.
[0056] Comparative Example 1
[0057] A Pt / NC oxygen reduction catalyst, the preparation method of which specifically includes the following preparation steps:
[0058] Dissolve 0.27 g of o-phenanthroline in 25 mL of an aqueous ethanol solution (V 乙醇 :V 水 The solution was mixed by sonication for 10 minutes (ratio 1:1). Then, 1.98 g of 2-methylimidazole and 0.5 g of SBA-15 were added to the mixture, and the mixture was stirred for 1 hour to ensure thorough mixing. The resulting solution was evaporated in a water bath at 70°C to obtain a white viscous substance. This substance was then dried overnight in an oven at 70°C to obtain a white solid. The white solid was then thoroughly ground to obtain the precursor.
[0059] The precursor was heated to 900°C in a nitrogen-filled tube furnace at a heating rate of 5°C / min and held at 900°C for 3 h. It was then cooled to room temperature at a rate of 5°C / min to obtain a black powder. The black powder was immersed in a 15 wt% HF solution for 12 h to etch the SBA-15 template. Finally, it was washed with deionized water until neutral and dried overnight under vacuum at 70°C to obtain the NC material.
[0060] Dissolve 0.3 g of NC material and 4.08 mL of H2PtCl6·6H2O aqueous solution (concentration 50 g / L) in 70 mL of a mixed solution of ethylene glycol and water (V 乙二醇 :V 水 The mixture was prepared with a 9:5 ratio of NaOH solution and thoroughly mixed. Then, an appropriate amount of 10 wt% NaOH solution was added to adjust the pH of the mixture to above 10. The thoroughly mixed solution was placed in a microwave reactor and heated to 400 K. Nitric acid was then added to adjust the pH of the reaction system to no higher than 2. After stirring for 2-5 minutes, the mixture was allowed to cool naturally, filtered, washed, and dried overnight under vacuum.
[0061] The dried solid powder was heated to 300℃ in a H2 / N2 mixture at a heating rate of 5℃ / min and held for 2h. Then the temperature was increased to 700℃ and held for 2h. The temperature was then lowered to room temperature to obtain a 20% Pt / NC catalyst.
[0062] Performance example 1
[0063] The oxygen reduction catalysts prepared in the above embodiments and comparative examples were subjected to the following electrochemical tests in a 0.1 M KOH solution using a three-electrode system, and their half-wave potentials (E0) were measured. 1 / 2 ), initial potential (E) onset ) and limiting diffusion current density (J L The ORR catalytic activity of the catalyst was evaluated. The Hg / HgO electrode was used as the reference electrode, and the platinum wire as the counter electrode. 3 mg of catalyst powder was dispersed in a mixed solution of ethanol and water containing 5 wt% Nafion (ethanol:water:Nafion = 40:9:1, V:V:V) to prepare a concentration of 3 mg·mL⁻¹. -1 A uniform slurry was ultrasonicated until stabilized, then dropped onto a glassy carbon electrode at a concentration of 6.5 μL. After drying, the working electrode was obtained. The obtained linear sweep voltammetry (LSV) curve is shown in the figure below. Figure 4 As shown in Table 1, the initial oxygen reduction performance index of each sample material in 0.1 M KOH solution is as follows:
[0064] Table 1
[0065] Example 1 (M1) 0.904 V 0.972 V <![CDATA[5.418 mA / cm 2 ]]> Example 2 (M2) 0.915 V 0.979 V <![CDATA[5.112 mA / cm 2 ]]> Comparative Example 1 (M3) 0.888 V 0.984 V <![CDATA[4.692 mA / cm 2 ]]> Commercial 20% Pt / C (m4) 0.894 V 0.969 V <![CDATA[5.153 mA / cm 2 ]]>
[0066] As shown in Table 1:
[0067] Half-wave potential (E) 1 / 2 The order is as follows: M2>M1>M4>M3;
[0068] Onset potential (E) onset The order is as follows: M3>M2>M1>M4;
[0069] Limiting diffusion current density (J) L The order is as follows: M1>M4>M2>M3.
[0070] Considering factors such as half-wave potential and limiting diffusion current density, the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Examples 1 and 2 exhibited the best initial oxygen reduction performance in 0.1 M KOH solution.
[0071] Performance example 2
[0072] The oxygen reduction catalysts prepared in the above embodiments and comparative examples were subjected to the following electrochemical tests in a 3.5 wt% NaCl solution using a three-electrode system, and their half-wave potentials (E0) were determined. 1 / 2 ), initial potential (E) onset ) and limiting diffusion current density (J LThe ORR catalytic activity of the catalyst was evaluated using a saturated calomel electrode as the reference electrode and a platinum wire as the counter electrode. 3 mg of catalyst powder was dispersed in a mixed solution of ethanol and water containing 5 wt% Nafion (ethanol:water:Nafion = 40:9:1, V:V:V) to prepare a concentration of 3 mg·mL⁻¹. -1 A uniform slurry was ultrasonicated until stabilized, then dropped onto a glassy carbon electrode at a concentration of 6.5 μL. After drying, the working electrode was obtained. The obtained LSV curve is shown in the figure below. Figure 5 As shown in Table 2, the initial oxygen reduction performance index of each sample material in 3.5 wt% NaCl solution is as follows:
[0073] Table 2
[0074] Example 1 (M1) 0.637 V 0.713 V <![CDATA[4.521 mA / cm 2 ]]> Example 2 (M2) 0.669 V 0.750 V <![CDATA[4.402 mA / cm 2 ]]> Comparative Example 1 (M3) 0.587 V 0.710 V <![CDATA[3.964 mA / cm 2 ]]> Commercial 20% Pt / C (m4) 0.616 V 0.714 V <![CDATA[4.162 mA / cm 2 ]]>
[0075] As shown in Table 2:
[0076] Half-wave potential (E) 1 / 2 The order is as follows: M2>M1>M4>M3;
[0077] Onset potential (E) onset The order is as follows: M2>M4>M1>M3;
[0078] Limiting diffusion current density (J) L The order is as follows: M1>M2>M4>M3.
[0079] Considering factors such as half-wave potential and limiting diffusion current density, the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Example 1 and Example 2 exhibited the best initial oxygen reduction performance in 3.5 wt% NaCl solution.
[0080] Performance Example 3
[0081] The oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1 were subjected to the following electrochemical tests in a three-electrode system in 0.1 M KOH solution. The durability of the catalysts was evaluated by a 12-h potentiostatic stability test (set at 0.6 V vs. RHE). Specifically... Figure 6 As shown.
[0082] Depend on Figure 6It can be seen that the 20% Pt / Fe-NC, 20% Pt / Co-NC and 20% Pt / NC catalysts prepared by Example 1, Example 2 and Comparative Example 1, as well as the commercial 20% Pt / C catalyst, had current retention rates of 83.19%, 67.71%, 69.37% and 78.05% respectively after 12 h of constant potential continuous discharge reaction.
[0083] Therefore, the 20% Pt / Fe-NC catalyst prepared in Example 1 has good stability in 0.1 M KOH solution.
[0084] Performance Example 4
[0085] The oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1 were subjected to the following electrochemical tests in a three-electrode system in 3.5 wt% NaCl solution. The durability of the catalysts was evaluated by a 12-h potentiostatic stability test (set at 0.4 V vs. RHE). Specifically... Figure 7 As shown.
[0086] Depend on Figure 7 It can be seen that the 20% Pt / Fe-NC, 20% Pt / Co-NC and 20% Pt / NC catalysts prepared by Example 1, Example 2 and Comparative Example 1, as well as the commercial 20% Pt / C catalyst, had current retention rates of 93.86%, 93.37%, 72.64% and 73.62% respectively after 12 h of constant potential continuous discharge reaction.
[0087] Therefore, it can be seen that the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Examples 1 and 2 have good stability in 3.5 wt% NaCl solution.
[0088] Performance example 5
[0089] The oxygen reduction catalysts prepared in Examples 1, 2, and Comparative Example 1 were mixed with a slurry prepared from a commercial 20% Pt / C catalyst at a concentration of 1 mg / cm³. 2 The loading was added to 1 cm 2 A magnesium-air battery was assembled on carbon paper using AZ31 as the anode and a 3.5 wt% sodium chloride aqueous solution as the electrolyte. The performance of the magnesium-air battery was evaluated using polarization curves, step discharge curves, and constant current discharge curves. Specifically... Figure 8 , Figure 9 and Figure 10 As shown.
[0090] Depend on Figure 8It can be seen that the peak power densities of the 20% Pt / Fe-NC, 20% Pt / Co-NC, and 20% Pt / NC catalysts prepared in Examples 1, 2, and Comparative Example 1, as well as the commercial 20% Pt / C catalyst, are 67.27, 77.55, 57.19, and 61.20 mW / cm², respectively. 2 ;
[0091] Depend on Figure 9 It can be seen that the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Examples 1 and 2 can provide higher voltages than the 20% Pt / NC catalyst prepared in Comparative Example 1 and the commercial 20% Pt / C catalyst at all tested current densities; specifically, at a discharge current density of 1 mA / cm², 2 At that time, the discharge voltages of 20% Pt / Fe-NC, 20% Pt / Co-NC, 20% Pt / NC, and commercial 20% Pt / C were 1.53 V, 1.47 V, 1.46 V, and 1.47 V, respectively; the discharge current density was 5 mA / cm². 2 At that time, the discharge voltages of each catalyst were 1.42 V, 1.38 V, 1.35 V, and 1.37 V, respectively; the discharge current density was 10 mA / cm². 2 At that time, the discharge voltages of each catalyst were 1.35 V, 1.32 V, 1.28 V, and 1.31 V, respectively; the discharge current density was 20 mA / cm². 2 At that time, the discharge voltages of each catalyst were 1.25 V, 1.24 V, 1.19 V, and 1.23 V, respectively; the discharge current density was 50 mA / cm². 2 At that time, the discharge voltages of each catalyst were 1.02 V, 1.05 V, 0.97 V, and 1.03 V, respectively. When the current density increased from 50 mA / cm²... 2 Restored to 5 mA / cm 2 At that time, the discharge voltage of the 20%Pt / Fe-NC battery recovered to 1.42 V, and the discharge voltage of the 20%Pt / Co-NC battery recovered to 1.38 V, both consistent with the initial 5 mA / cm² discharge voltage. 2 The test values are basically consistent, indicating that it has good rate adaptability and discharge recoverability.
[0092] Depend on Figure 10 It can be seen that the magnesium-air batteries assembled with the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Examples 1 and 2 operate at 10 mA / cm². 2It can operate for more than 350 h at a constant current density. When discharged for 350 h, the voltage of the magnesium-air battery driven by 20% Pt / Fe-NC decreased from the initial 1.34 V to 1.30 V, and the voltage of the magnesium-air battery driven by 20% Pt / Co-NC decreased from the initial 1.33 V to 1.28 V. Its voltage loss is significantly lower than that of commercial 20% Pt / C (decreased from the initial 1.32 V to 1.26 V) and the 20% Pt / NC catalyst prepared in Comparative Example 1 (the voltage decreased from the initial 1.30 V to 1.17 V after 290 h of discharge).
[0093] The performance test results above show that the 20% Pt / Fe-NC and 20% Pt / Co-NC catalysts prepared in Examples 1 and 2 of this invention not only exhibit high catalytic activity in the alkaline oxygen reduction test, but also demonstrate superior chlorine resistance stability in 3.5 wt% NaCl chloride-containing electrolyte. In particular, they show better resistance to chlorine in the presence of transition metals (MN). x Compared to the 20% Pt / NC catalyst and the commercial 20% Pt / C catalyst, the catalyst of this invention exhibits a significantly improved 12-h current retention rate in chloride-containing electrolytes, indicating that the ordered mesoporous MNC support and MN... x The synergistic structure formed between coordination centers and Pt particles is a key factor in improving resistance to oxychloride reduction.
[0094] Furthermore, when a magnesium-air battery is assembled using the catalyst of this invention as an air electrode catalytic material, the battery can maintain a high output voltage and long-term discharge stability in a chloride-ion-containing electrolyte. This indicates that the catalyst of this invention is not only suitable for conventional oxygen reduction reaction test systems, but also for metal-air battery application scenarios under chloride-ion-containing electrolyte conditions such as sodium chloride aqueous solution, simulated seawater, or natural seawater.
Claims
1. A supported platinum-based catalyst for oxygen reduction reactions in chloride-containing electrolytes, characterized in that, The MNC carrier includes an ordered mesoporous structure and Pt particles loaded on the MNC carrier, wherein M is at least one of Fe, Co, Ni, Mn, Cu, and Zn, and the MNC carrier contains MN. x The Pt particles, acting as coordination centers, are dispersed on the outer surface, pores, and / or mesoporous channels of the MNC support. This ordered mesoporous structure facilitates the dispersion of Pt particles and reactant mass transfer, and can regulate the Cl content. - The local diffusion environment of the electrolyte near the Pt active sites; the MN x The coordination center can interact with Pt particles to form a metal-support interaction, thereby modulating the electronic structure of the Pt particles. M is preferably Fe and / or Co.
2. The supported platinum-based catalyst according to claim 1, characterized in that, The Pt in the catalyst has a mass fraction of 5-50 wt%, preferably 10-30 wt%.
3. A method for preparing the supported platinum-based catalyst according to any one of claims 1-2, characterized in that, Includes the following steps: (1) Add the precursor of metal element M and the heterocyclic compound with bidentate nitrogen ligand to the alcohol-water mixture and disperse by ultrasonication to obtain mixed solution A; (2) Add and disperse the nitrogen-containing compound and mesoporous template into the mixed solution A, and stir to mix them evenly to obtain mixed solution B; (3) After drying the mixed solution B, a solid powder was obtained; the solid powder was pyrolyzed at high temperature under an inert atmosphere, and then washed and dried with hydrofluoric acid to obtain an MNC carrier with an ordered mesoporous structure. (4) Add the MNC carrier and H2PtCl6·6H2O or its aqueous solution to a mixed solution of ethylene glycol and water, sonicate and stir to obtain solution C, and add NaOH solution to adjust the pH value of solution C to not less than 10; (5) Place solution C in a microwave reactor and heat to 400 K. Then add nitric acid to adjust the pH of the reaction system to no higher than 2. Stir for 2-5 min and then cool naturally. Filter, wash and vacuum dry to obtain Pt / MNC precursor powder. (6) The Pt / MNC precursor powder is heated in a reducing atmosphere to obtain the Pt / MNC catalyst.
4. The method according to claim 3, characterized in that, The precursor of the metal element M in step (1) includes at least one of sulfate, chloride, acetate, and aromatic organometallic compound; the metal element M includes at least one of Fe, Co, Ni, Mn, Cu, and Zn, preferably Fe and / or Co; The heterocyclic compound with bidentate nitrogen ligands in step (1) includes at least one of o-phenanthroline and bipyridine; the molar ratio of the metal element M to the heterocyclic compound with bidentate nitrogen ligands is 1:(1~6), preferably 1:2~1:
3.
5. The method according to claim 3, characterized in that, The nitrogen-containing compound in step (2) is selected from one or more of 2-methylimidazole, dicyandiamide, urea, pyridine, pyrrole, and melamine; the molar ratio of the transition metal precursor to the nitrogen-containing compound is 1:6 to 1:60, preferably 1:30 to 1:45; The mesoporous template in step (2) is selected from at least one mesoporous silica template among SBA-15, MCM-48, and KIT-6. The mesoporous template is used to induce the formation of an ordered mesoporous channel structure that can buffer Cl⁻ diffusion.
6. The method according to claim 3, characterized in that, The pyrolysis atmosphere in step (3) is nitrogen or argon, the pyrolysis temperature is 800~1000℃, the pyrolysis time is 1.5~5 h, and the heating rate from room temperature to the pyrolysis temperature is 2~5℃ / min.
7. The method according to claim 3, characterized in that, The reducing atmosphere in step (6) is a mixture of H2 / N2 or H2 / Ar, and the heating is a two-stage heat treatment. The first-stage treatment temperature is 200~400℃ to achieve preliminary reduction, and the second-stage reduction treatment temperature is 600~800℃ to establish a strong interaction between the metal and the carrier. The holding time for each temperature plateau is 1.5~2 h, and the heating rate from room temperature to the corresponding treatment temperature is 2~5℃ / min.
8. The application of the supported platinum-based catalyst according to any one of claims 1-2 in the catalysis of oxygen reduction reaction in chloride-containing electrolytes.
9. The application according to claim 8, wherein the chloride-containing electrolyte is preferably an aqueous solution of sodium chloride, simulated seawater, or natural seawater, and the chloride-containing electrolyte contains Cl... - The concentration is 0.1~1.0 mol / L, or the concentration of the sodium chloride aqueous solution is 0.5~5 wt%.
10. The application according to claim 8, in the air electrode of a metal-air battery; wherein the metal-air battery uses a chloride-containing electrolyte, preferably an aqueous solution of sodium chloride, simulated seawater, or natural seawater; and wherein the metal-air battery is preferably a magnesium-air battery.